2019
DOI: 10.1088/1748-9326/ab142c
|View full text |Cite
|
Sign up to set email alerts
|

Framework of multidimensional macrobenthos biodiversity to evaluate ecological restoration in wetlands

Abstract: Sustaining biodiversity is a priority for ecological restoration in degraded wetlands, and biodiversity is an inherently multidimensional ecosystem property, as it includes genetic, taxonomic, functional, and other types of diversity. However, most restoration projects have only employed taxonomic diversity to assess restoration, and given the multidimensional nature of biodiversity, this may partially describe the true situation. In this paper, we constructed a multidimensional macrobenthos biodiversity frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…We further used a binary coding approach (i.e., 1 if a species displays a trait attribute, 0 if not) to encode trait attributes of the macrobenthos collected in the river-lake system (Supplementary Table 2; Li et al, 2019a,c;Li S. H. et al, 2020;Juvigny-Khenafou et al, 2021). Information regarding the functional traits of macrobenthos 10.3389/fevo.2022.922539 was mainly obtained from the published literature on freshwater ecosystem (Li et al, 2019a;Zhang et al, 2019;Li Z. F. et al, 2020;Dolédec et al, 2021;Juvigny-Khenafou et al, 2021;Peng et al, 2021). Where the trait attributes of a given species were not available, we used information from other species within the same genus or family (Sivadas et al, 2021;Paz et al, 2022).…”
Section: Functional Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…We further used a binary coding approach (i.e., 1 if a species displays a trait attribute, 0 if not) to encode trait attributes of the macrobenthos collected in the river-lake system (Supplementary Table 2; Li et al, 2019a,c;Li S. H. et al, 2020;Juvigny-Khenafou et al, 2021). Information regarding the functional traits of macrobenthos 10.3389/fevo.2022.922539 was mainly obtained from the published literature on freshwater ecosystem (Li et al, 2019a;Zhang et al, 2019;Li Z. F. et al, 2020;Dolédec et al, 2021;Juvigny-Khenafou et al, 2021;Peng et al, 2021). Where the trait attributes of a given species were not available, we used information from other species within the same genus or family (Sivadas et al, 2021;Paz et al, 2022).…”
Section: Functional Diversitymentioning
confidence: 99%
“…The macrobenthos community show a range of life history characteristics (e.g., relatively long lifespans, sedentary existence), and play a central role in energy flows and material circulation in aquatic ecosystems (Li et al, 2019a;Mosbahi et al, 2019). In general, the macrobenthos have been regarded as key biological indicators of freshwater ecosystem health because these organisms are in direct contact with the sediment and are highly sensitive to changes in physiochemistry of the environment (Soldner et al, 2004;O'Brien et al, 2016;Piló et al, 2016;Eriksen et al, 2021).…”
mentioning
confidence: 99%
“…We chose Patrick's index, Shannon‐Weiner's index, Simpson's index, and Alatalo's evenness index to represent the taxonomic diversity in our study because each diversity metric reflects a different aspect of the macrophyte community, and the different aspects cannot be adequately described using only one index (X. X. Li, Yang, Sun, & Su, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Fu et al study the macrobenthos biodiversity patterns in the river-lake ecotones along the Fu River-Baiyangdian Lake gradient in northern China (Wang et al, 2019;Mishra et al, 2022b). The article found that water depth, water transparency, TN, and TP were the main drivers of macrobenthos taxonomic and functional diversity, while sediment Cd, Cr, Cu, Pb, and Zn contents also had an impact on macrobenthos diversity (Li et al, 2019;Mosbahi et al, 2019). The article suggests that functional diversity approaches based on biological traits can complement taxonomic approaches in river-lake ecotones.…”
Section: Biodiversity and Food Web Analysismentioning
confidence: 98%